Kebahagiaan Dalam Perspektif Kajian Psikologi Raos - Muniroh, Alimul (MADINAH, 2017)
Developing a science based on indigenous knowledge not only in the religious sciences, but also in other scientific fields, including psychology. The emergence of raos psychology can be interpreted to be a milestone in the development of psychology of nusantara.Tulisan aims to peel the psychology of raos derived from the thought of Ki Ageng Suryomentaram as part of indigeneus psychology characterized by raising indigenous knowledge to a more universal aspect. In addition, this paper takes the perspective of raos psychology to dissect the happiness of human life.Why happiness? One of the goals of life of a human being is to seek happiness. In a positive positive psychology it is attributed directly to the attainment of matter. But in the perspective of the psychology of happy raos can occur when humans successfully manage karep (desire) so that human happiness can be more lasting.